COMPLEXITIES IN DEALING WITH GENDER INEQUALITY: Muslim Women and Mosque-Based Social Services in East Java Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
This paper applies an Islamic legal sociology approach to criticize the typology of East Java society and their views on gender equality, women's empowerment, and women's roles in mosques based on the subcultures of East Java community: Mataraman, Tapal kuda, and Arek'an. The concept of male-female equality has not been fully accepted by religious leaders. There is a power relation in the Muslim society’s high-power structure because religious leaders are still dominated by men while women are considered as subordinate and marginal groups. On the one hand, there is still a patriarchal cultural-based political configuration that affects gender discrimination. On the other hand, the Muslim community has not been completely established to protect women. Finally, the finding of this paper is that the role of mosque-based women in three sub-cultures of East Java shows different results. The subculture of Mataraman tends to be culture-based, whereas religion is considered as a supporting factor. The subculture of Tapal Kuda prefers to collaborate religious views with patriarchal cultures. Finally, the subculture of Arek'an is likely to dialogue religion with culture more inclusively. A progressive mosque that provides women's empowerment may break the chain of the gender-biased understanding and change the mindsets of patriarchal Muslim societies through dialogue, social interaction, and productive activities.